A qualitative examination of yoga for middle school adolescents. Issue 3 (3rd July 2017) - Butzer, Bethany; LoRusso, Amanda Marie; Windsor, Regina; Riley, Frankye; Frame, Kate; Khalsa, Sat Bir S.; Conboy, Lisa
Abstract: The present study was part of a group randomized controlled trial in which 7th grade students were assigned to a yoga intervention or physical-education-as-usual. Sixteen students were randomly selected from the yoga condition to participate in one-on-one interviews. Qualitative analyses revealed 13 themes that were organized into two categories: Usability (student perceptions of the usefulness, learnability, and convenience of the yoga intervention) and Effect (student perceptions of the direct results of the yoga intervention). Students reported both positive and negative opinions of yoga, especially when making direct comparisons between yoga and physical education. Students had particularly positive opinions regarding the beneficial effects of yoga on stress, sleep, and relaxation. Student opinions regarding the effects of yoga on self-regulation, social interaction, substance use, and academic performance were also generally positive, although somewhat mixed. Results suggest that qualitative research shows promise for providing an in-depth perspective on the impact of mind-body interventions in schools.